The use of anticoagulants in the management of atrial fibrillation among general practices in England. Issue 16 (7th February 2013) - Cowan, Campbell; Healicon, Richard; Robson, Ian; Long, W Robert; Barrett, James; Fay, Matthew; Tyndall, Keith; Gale, Chris P
Abstract : Objectives: To investigate the use of oral anticoagulants (AC) and antiplatelet agents (AP) in the management of atrial fibrillation (AF) among patients in primary care in England. Design: Epidemiological study. Setting: 1857 general practices in England representing a practice population of 13.1 million registered patients. Patients: 231 833 patients with a history of AF. Main outcome measures: The primary outcome was AC and AP use by CHADS2 score and age groups <30 years, 30–49 years, 50–64 years, 65–79 years and >79 years. Results: 231 833 patients with a history of AF were identified, giving a prevalence among uploading practices of 1.76%. Prevalence of AF varied markedly between practices, related to differing practice age profiles. The total number of patients with AF in a practice was strongly predicted by the number of patients aged 65 years and over in the practice. 57.0% of the AF population had a CHADS2 score ≥2 and 83.7%≥1. 114 212 (49.3%) patients received AC therapy. AC uptake increased with increasing CHADS2 score up to a score of 3, but thereafter reached a plateau. Among 132 099 patients with a CHADS2 score ≥2, 72 211 (54.7%) received an AC, 14 987(11.3%) were recorded as having a contraindication or having declined AC therapy, leaving 44 901 (34.0%) not on AC therapy and without a recorded contraindication or recorded refusal. Among patients not prescribed an AC, 79.9% were prescribed an AP. The use of AC declined in the elderly (for CHADS2 ≥2, 47.4% of patients ≥80 years, compared with 64.5% for patients aged <80 years, p<0.001). By contrast, AP uptake was more prevalent among elderly patients. Conclusions: Over one-third of patients with AF and known risk factors who are eligible for AC do not receive them. There is a high use of AP among patients not receiving AC. Uptake of AC is particularly poor among patients aged 80 years and over.